ABUNDANCE AND ISOTOPIC COMPOSITION OF PLANKTONIC MICROCRUSTACEANS IN A CENTRAL AMAZON FLOODPLAIN LAKE: IMPLICATIONS FOR THE TROPHIC DYNAMICS OF THE PLANKTON COMMUNITY - Pedro Caraballo; Bruce Forsberg; Rosseval Leite (Caldasia)
During the hydrological year from December 2007 to November 2008, monthly samplings in the pelagic, littoral and macrophytes zones were conducted in the Lago Catalão, a floodplain lake receiving a mixture of water from Negro and Solimões Rivers, in front of Manaus city. Taxonomic composition and their relative abundance of the planktonic microcrustaceans community was studied. Natural abundances of carbon (C) and nitrogen (N) stable isotopes were measured to indicate energy sources. Cladocerans were the most abundant, with a relative abundance of 60%, followed by the calanoid and cyclopoid copepods with relative abundances of 29% and 11%, respectively. Diaphanosoma spp. was the dominant cladoceran group during all the sampling periods. Cladocerans were also represented by Moina spp., Ceriodaphnia spp. and Daphnia gessneri. Three genera of calanoid copepods were found: Notodiaptomus spp, Rhacodiaptomus spp., and Argyrodiaptomus spp. The genus Mesocyclops spp. was identified among the cyclopoid copepods. Zooplankton δ13C values indicated that the aquatic macrophyte zone was distinct, with a mean of -27.31‰, which was more enriched than zooplankton in the pelagic and littoral zones, where they had mean δ13C values of -33.11 and -34.66‰, respectively. Overall, analysis of stable isotopes showed that regardless of the pathways, the initial source of carbon for the zooplankton was phytoplankton, with a minimal participation of heterotrophic bacteria.